1990
DOI: 10.1029/wr026i009p02171
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm growth and the related changes in the physical properties of a porous medium: 3. Dispersivity and model verification

Abstract: In the first part of this paper the change in dispersivity resulting from the growth of a biofilm in a porous medium is derived from an existing model of dispersivity and a cut‐and‐random‐rejoin‐type model of the pore geometry. The change in dispersivity due to a biofilm is also estimated from experimental data. Tracer experiments were conducted in biofilm column reactors and dispersion coefficients estimated by solving the inverse solute transport problem by nonlinear, least squares regression. Due to the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(50 citation statements)
references
References 8 publications
6
40
1
Order By: Relevance
“…Finally, Eqs. (12) and (13) can be simplified and the resulting set of macroscopic equations is the following:…”
Section: Illustrative Scenarios Of Equilibrium and Non Equilibrium Comentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, Eqs. (12) and (13) can be simplified and the resulting set of macroscopic equations is the following:…”
Section: Illustrative Scenarios Of Equilibrium and Non Equilibrium Comentioning
confidence: 99%
“…The assumption that the reactive phenomena do not prevail over the convective and diffusive processes, i.e., Da Ac 6 Pe A and Da Ax 6 Pe A ; is required to overcome this difficulty. These closure fields are used to evaluate the effective parameters of the macroscopic equation, according to the following expressions, which are derived by the injection of the closure assumptions (12) and (13) in the unclosed macroscopic equations (10) and (11). …”
Section: ðB:41þmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, planktonic bacterial density (Batchelor et al 1997;Lehman et al 2001;O'Toole et al 2000), tracer experiments (Hill and Sleep 2002;Taylor and Jaffé 1990), and monitoring of terminal electron accepting conditions, via oxidation-reduction potential (ORP) probes (Appelo and Postma 1993;Bishop and Yu 1999;Kamon et al 2002), have been reported. Again, little information exists on the application of such techniques in fractured media.…”
Section: Introductionmentioning
confidence: 97%
“…In this section we investigate the impact of this condition on the final results, as well as the 637 additional uncertainty introduced. Also, several experiments reported a medium to large increase in 638 dispersivity together with the reduction in porosity and permeability (Taylor and Jaffé, 1990c growth. We will use numerical experiments to investigate the extent to which such process can con-642 tribute to an increase of dispersivity.…”
mentioning
confidence: 99%